'Rapid speed of response to ECT in bipolar depression: A chart review. (March 2022) - Scheepstra, K.W.F.; van Doorn, J.B.; Scheepens, D.S.; de Haan, A.; Schukking, N.; Zantvoord, J.B.; Lok, A.
Abstract: Objective: To validate a faster speed of response to electroconvulsive therapy (ECT) for bipolar depression (BPD) compared to major depressive disorder (MDD) Method: Retrospective chart review on an ECT cohort in an academic hospital setting. Speed of response was defined by the number of ECT treatments needed for response or remission. Results: Sixty-four depressed patients were included, of whom 53 (MDD: 40, BPD: 13) could be analyzed. The bipolar group responded faster with a mean difference of 3.3 fewer ECT treatments to meet response criteria (MDD 10.4 vs. BPD 7.1, p = 0.054). When using mixed effects regression models for the response/remitter group (n = 35), a faster response for the bipolar group (AIC 252.83 vs 258.55, χ 2  = 11.72, p = 0.008) was shown. Other factors, such as psychotic features or comorbidity, did not influence the speed of response. Conclusion: This chart review of an ECT cohort in an naturalistic academic hospital setting shows an evident and clinically relevant faster speed of response in bipolar depression. Highlights: Patients with bipolar depression show a more rapid response to electroconvulsive therapy (ECT) compared to patients with major depressive disorder. The bipolar group received an average of 3.3 fewer ECT treatments to meet response criteria. This difference is not driven by episode features, refractoriness or comorbidity, such as psychotic features or personality disorders/traits.